UJI COBA PEMANENAN GETAH PULAI DARAT (Alstonia angustiloba Miq.) MENGGUNAKAN STIMULAN ORGANIK - Sarah Andin; Mutia Herni Ningrum; Sukadaryati; Soenarno (BRIN Publishing, 2022)
The utilization of the pulai darat tree (Alstonia angustiloba Miq.) is not only for wood but also for sap. The potency ofpulai darat in KHDTK Kemampos is relatively abundant and its sap has not been utilized optimally. This paper observes thetapping techniques and an additional stimulants for enhancing sap production. This study aimed to explore the optimum tappingtechniques and the use of stimulants to improve pulai darat sap production. The combination of two tapping techniques and threestimulants were observed in this study. Result shows that the V-shape tapping produced more sap than half spiral-shape tappingtype and organic stimulants could improve sap production compared to those without stimulants. In this study, wood vinegarstimulants produced the highest sap followed by lime with an average production of 16.75 g and 12.40 g, respectively. Therefore,further tapping innovation is necessary to develop an efficient and effective stem wounding process and stimulants application.